Policy and public management on earthquakes - Tirton Nefianto (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Disasters are the result of extraordinary events (hazards) occurring in vulnerable communities at a time when the community is unable to cope with the various implications of these extraordinary events. This study aims to determine public policy and management regarding earthquakes. The research method used is a qualitative one. Data collection was carried out using a literature review related to policies and public handling related to the earthquake disaster. The results of this study state that it is necessary to map earthquake-prone areas, which should be carried out by research institutions. Central and regional government policies as well as to increase public awareness of disaster threats. There is a need for rules regarding zoning and building construction, both for office housing and public facilities, with earthquake-resistant construction so as to minimize casualties. These rules must be followed by the following inspections before and during the construction of the building: For people who can't afford it, volunteers are provided to help provide input in building earthquake-resistant buildings. This second approach is often called structural mitigation because it places more emphasis on strengthening the entire physical structure. The third to fifth approaches are usually called non-structural mitigation. So that with the existence of policies and public management, it is hoped that they can provide solutions and countermeasures in handling earthquake disasters.